Farming systems surveys with farmers from the rural commune of Ait Ichou, Khemisset, Morocco - Amri, Ahmed; Boughlala, Mohamed; Sahri, Ali; Imtiaz, Muhammad; Bishaw, Zewdie (2025)
Farming systems surveys with farmers from the rural commune of Ait Ichou, Khemisset, Morocco.